2022
DOI: 10.1017/gmh.2021.48
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among adolescents in India: a systematic review

Abstract: Background Alcohol use is typically established during adolescence and initiation of use at a young age poses risks for short- and long-term health and social outcomes. However, there is limited understanding of the onset, progression and impact of alcohol use among adolescents in India. The aim of this review is to synthesise the evidence about prevalence, patterns and correlates of alcohol use and alcohol use disorders in adolescents from India. Methods Systematic review was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 79 publications
2
14
0
Order By: Relevance
“…Over 60% of reported current drinkers also revealed that they started drinking either because they felt like it, or due to peer pressure. This corroborates findings from previous studies conducted in Africa and Europe (Gowin et al, 2017;Howell et al, 2010;Nadkarni et al, 2022). Similar studies in the United States and Australia revealed higher drinking and binge drinking among adolescents who have friends and peers who drink than those who did not have friends or peers who drink (Cheadle et al, 2015;Rüütel et al, 2014).…”
Section: Patterns Of Drinking Among Participants In the Last Yearsupporting
confidence: 89%
See 2 more Smart Citations
“…Over 60% of reported current drinkers also revealed that they started drinking either because they felt like it, or due to peer pressure. This corroborates findings from previous studies conducted in Africa and Europe (Gowin et al, 2017;Howell et al, 2010;Nadkarni et al, 2022). Similar studies in the United States and Australia revealed higher drinking and binge drinking among adolescents who have friends and peers who drink than those who did not have friends or peers who drink (Cheadle et al, 2015;Rüütel et al, 2014).…”
Section: Patterns Of Drinking Among Participants In the Last Yearsupporting
confidence: 89%
“…Significant associations (p < 0.001) were also observed for institution and course of study. The higher prevalence of reported alcohol consumption observed among the study participants could be due to poor coping skills, easy access to alcohol, and positive expectations regarding alcohol use (Gowin et al, 2017;Howell et al, 2010;Nadkarni et al, 2022).…”
Section: Prevalence Of Reported Current Drinking and Audmentioning
confidence: 88%
See 1 more Smart Citation
“…Besides, in many countries of the three regions, alcohol consumption starts before 15 years and could be 50–70% among 15‐years‐old people (WHO, 2019). Similarly, a recent systematic review in India has indicated that lifetime alcohol consumption among adolescents could be 69.8% (Nadkarni et al., 2022).…”
Section: Introductionmentioning
confidence: 97%
“…among 15-years-old people (WHO, 2019). Similarly, a recent systematic review in India has indicated that lifetime alcohol consumption among adolescents could be 69.8% (Nadkarni et al, 2022).…”
Section: Introductionmentioning
confidence: 98%